2017
DOI: 10.1002/cne.24288
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the axon initial segment of mice substantia nigra dopaminergic neurons

Abstract: The axon initial segment (AIS) is the site of initiation of action potentials and influences action potential waveform, firing pattern, and rate. In view of the fundamental aspects of motor function and behavior that depend on the firing of substantia nigra pars compacta (SNc) dopaminergic neurons, we identified and characterized their AIS in the mouse. Immunostaining for tyrosine hydroxylase (TH), sodium channels (Na ) and ankyrin-G (Ank-G) was used to visualize the AIS of dopaminergic neurons. Reconstruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 66 publications
6
32
3
Order By: Relevance
“…Conductance values were set according to our own measurements or published values (Table 1). Consistent with the literature (Zhou et al, 1998;Kole et al, 2008;Hu et al, 2009;González-Cabrera et al, 2017), g Na and g KDR densities are higher in the AIS than in the rest of the neuron so that AP always initiates in the AIS. According to Gentet and Williams (2007), I A density and inactivation kinetics were higher and depolarized, respectively, in the soma compared with the dendritic arbor.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…Conductance values were set according to our own measurements or published values (Table 1). Consistent with the literature (Zhou et al, 1998;Kole et al, 2008;Hu et al, 2009;González-Cabrera et al, 2017), g Na and g KDR densities are higher in the AIS than in the rest of the neuron so that AP always initiates in the AIS. According to Gentet and Williams (2007), I A density and inactivation kinetics were higher and depolarized, respectively, in the soma compared with the dendritic arbor.…”
Section: Methodssupporting
confidence: 90%
“…Moreover, as shown in Figure 2D, most of the variation in soma-AIS distance was due to variation in ABD stem length. Therefore, consistent with previous studies (Häusser et al, 1995;Blythe et al, 2009;González-Cabrera et al, 2017;Meza et al, 2018), we found large variations in AIS length, soma-AIS distance, but also in dendrite and axon diameter between SNc DA neurons.…”
Section: Variability Of Axon Location and Ais Geometry In Snc Da Neuronssupporting
confidence: 93%
“…We found that OB AISes are of reasonably consistent length (coefficient of variation, CV = 0.34 in control cells), but can be situated at highly variable distances from the soma (control CV = 0.75). Contrary to findings in midbrain DA cells (González-Cabrera et al, 2017;Meza et al, 2018) and in OB dissociated cultures (Chand et al, 2015) we found no consistent relationship between these parameters in bulbar DA neurons (Spearmen coefficient of AIS length vs soma distance: Ctrl r=0.03, Occl, r=0.04; both p>0.73). We also noted that that the AIS of an OB DA neuron can be located either on a process that directly emanates from the soma ("soma-origin" AIS), or on a process separated from the soma by one or more branch nodes ("dendrite-origin" AIS, Ctrl n=31, Occl n=33; Fig.…”
Section: Da Cells Equipped With An Axon Shorten Their Axon Initial Secontrasting
confidence: 99%
“…We also noted that that the AIS of an OB DA neuron can be located either on a process that directly emanates from the soma ("soma-origin" AIS), or on a process separated from the soma by one or more branch nodes ("dendrite-origin" AIS, Ctrl n=31, Occl n=33; Fig. 8A-B) (González-Cabrera et al, 2017;Höfflin et al, 2017;Houston et al, 2017;Kosaka et al, 2019;Thome et al, 2014;Yang et al, 2019). While this peculiar axonal arrangement challenges the traditional view on neuronal input-output transformation (Kaifosh and Losonczy, 2014), it is not unique to bulbar DA neurons.…”
Section: Da Cells Equipped With An Axon Shorten Their Axon Initial Sementioning
confidence: 90%
See 1 more Smart Citation